Metabolische Führung und Ernährung von Intensivpatienten mit renaler Dysfunktion = Metabolic management and nutrition in critically ill patients with renal dysfunction.Recommendations from the renal section of the DGIIN, ÖGIAIN, and DIVI - Druml, Wilfred; Kindgen-Milles, Detlef (Medizinische Klinik, Intensivmedizin und Notfallmedizin, 2018)
BackgroundIntensive care patients with renal failure or insufficiency comprise a heterogeneous group of subjects with widely differing metabolic patterns and nutritional requirements. They include subjects with various stages of acute kidney injury (AKI), acute-on-chronic renal failure (A-CKD), without/with renal replacement therapy (RRT), chronic kidney disease (CKD), and subjects on regular hemodialysis or peritoneal dialysis therapy (HD/PD).GoalsDevelopment of recommendations by the renal section of DGIIN (Deutsche Gesellschaft für Internistische Intensivmedizin und Notfallmedizin), ÖGIAIN (Österreichische Gesellschaft für Internistische und Allgemeine Intensivmedizin und Notfallmedizin) and DIVI (Deutsche Interdisziplinäre Vereinigung für Intensiv- und Notfallmedizin) for the metabolic management and the planning, indication, implementation, and monitoring of nutrition therapy in this heterogeneous group of patients.Materials and methodsThe recommendations are based on recent evidence and current recommendations of DGEM (Deutsche Gesellschaft für Ernährungsmedizin), ASPEN (American Society for Parenteral and Enteral Nutrition) and ESPEN (European Society for Clinical Nutrition and Metabolism) and also the KDGIO (Kidney Disease: Improving Global Outcomes) clinical practice guidelines for AKI and the expert knowledge and clinical experience of the authors.ResultsNutrition support in these patient groups is not fundamentally different from that in other disease states but must consider the multiple variations in metabolism and nutrient requirements. Nutrition therapy must be adapted to the stage of disease and especially, in those patients on RRT. Nutritional needs can differ widely between patients but also in the same patient during the course of the disease.ConclusionsThus, the patient with renal failure requires an individualized approach in nutrition support and because of the altered metabolism of many nutrients and intolerances for electrolytes and fluids, the nutrition support in patients with renal insufficiency requires close clinical and laboratory monitoring.